Naltrexone Reverses Ethanol-Induced Rat Hippocampal and Serum Oxidative Damage - Almansa, Inmaculada (Hindawi Publishing Corporation, 2013)
Naltrexone, an antagonist of μ-opioid receptors, is clinically used as adjuvant therapy of alcohol dishabituation. The aim of the present work was to test the effect of 1 mg/kg body weight of naltrexone to revert oxidative stress-related biochemical alterations, in the hippocampus and serum of chronic alcoholic adult rats. Malondialdehyde concentration was increased and glutathione peroxidase activity was decreased in hippocampus and serum of alcohol-treated rats. Naltrexone treatment restored these alterations. The in vitro antioxidant ability of Ntx could not justify these effects considering the doses used. Thus this apparent protective effect of Ntx can only be attributed to its pharmacological effects, as herein discussed.